Traditional Anti Malaria Plants Species of Balikpapan Botanic Garden, East Kalimantan-Indonesia - Kuswantoro, Farid (KnE Life Sciences, 2017)
Numerous Kalimantan plants species were traditionaly utilized for its medicinal properties. Ex situ conservation of these species in Balikpapan Botanic Garden (BBG), one of the mostly recent launched botanic garden in Indonesia however, should be appreciated and encouraged to preserved the unique traditional plant-based medicine knowledge of Kalimatan people. An etnobotany literature study was conducted to documented traditional medicine plant species collected in BBG used by indigenous people of Kalimantan to treat malaria. This study found nine plant species collected in BBG namely Aleurites mollucanus (L.) Willd., Alstonia angustiloba Miq., Alstonia scholaris L. R. Br., Areca catechu L., Eurycoma longifolia Jack, Lansium parasiticum (Osbeck) K. C. Sahni & Bennet, Morinda citrifolia L., Peronema canescens Jack and Vitex pinnata L. were traditionally used to treat malaria. Further literature study showed that some of these species exhibits biological activity toward Plasmodium berghei and P. falciparum. Three species of this list were classified as rare medical plants in Indonesia. However, further study will still be needed to fully confirm anti malaria activity of these plant species and its potential to become new anti-malaria medicine. Keywords: Balikpapan Botanic Garden; ex situ conservation; Malaria; traditional medicine